PENAMBAHAN MINYAK ATSIRI RIMPANG BANGLE (ZINGIBER PURPUREUM ROXB.) SEBAGAI ANTIBAKTERI TERHADAP KARAKTERISTIK SENSORI SABUN CAIR - Dewi Wulandari; Akhyar Ali2; Dewi Fortuna Ayu (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this study was to determine the quality of sensory and antibacterial activity of liquid soap with the addition of essential oil bangle rhizome. This study used a Complete Randomized Design with five treatments and  three  replications.  The  treatments  were  addition  of  essential  oils  in consecutive S0 (0 ml), S1 (0,62 ml), S2 (1,24 ml), S3 (1,86 ml), and S4 (2,5 ml). The data obtained were analyzed statistically using Analysis of Variance dan Duncan’s New Multiple Range Test at 5%. The research showed that addition of bangle   rhizome   essential   oils   significantly   effected   on   descriptive test and hedonic test. The best treatment of liquid soap in this research was S4 (addition bangle essential oil 2,5 ml) which had result of descriptive test on liquid soap showed that soap had very bangle scents and hedonic test on liquid soap scents was not favored by the panelists. Keywords:  Bangle  (Zingibeer  purpureum  Roxb.),  essential  oil,  liquid  soap, antibacterial